The indexing of the Al-Kindy College Medical Journal in the Scopus Database Journals: A Fundamental Step toward an International Recognition - Al-Mendalawi, Mahmood D.; Hameed, Ekhlas Khalid; Al-Ameri, Laith Thamer (AL-Kindy College Medical Journal, 2023)
On Saturday, May 13, 2023, a glorious day was engraved in the history of Al-Kindy College Medical Journal as it is the day of indexing the journal in the Scopus Database Journals. The journal has paced a strenuous journey to make that achievement.